The National Collegiate Athletic Association : is 'one and done' both legal and moral? - Kase, Matthew; Nolan, Christopher, active 2019; O'Rourke, James S., 1946- (London : The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame, 2019)
Since 2005, the nation's top-ranked high school basketball prospects (and future NBA players) have been forced to delay their NBA draft declarations by one year. The 'One-and-Done' rule has faced harsh scrutiny for a number of reasons, and recent corruption in the college basketball world has only intensified the issue. This case explores the history of the rule, how it has affected young athletes, and whether it is the best solution for athletes and institutions of higher learning.
Originally Published In Kase, M., Nolan, C., & O'Rourke, J. S. (2019). The National Collegiate Athletic Association: Is 'One and Done' Both Legal and Moral?. 19-13. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; National Collegiate Athletic Association -- Rules and practice; Basketball players -- Selection and appointment -- United States